Estimation of Some Life-History Parameters from Length at First Maturity of African Catfish Clarias Gariepinus (Burchell, 1822) Cultured Under 0l: 24d Photoperiod Using Empirical Equations - Mustapha, Moshood Keke (Malaysian Journal of Science, 2016)
Estimation of some life history parameters such as length (L), weight (W), mortality (M), population food consumption (Q/B), gross food conversion efficiency (GE), von Bertalanffy growth factor (K) and life span (tmax) using empirical equations was conducted on Clarias gariepinus reared in triplicate in the 0L: 24D photoperiod. The mean length and weight at first maturity was 45.7 ±0.2cm, and 728.13 ± 0.5g respectively. Highest temperature recorded was 27 °C. Estimate of optimum length (Lopt) was 49.1 cm, mortality was 2.37/year and 1.18 for the 6-month cultured period, food consumed and gross food conversion efficiency was 8.7 and 0.181 respectively. The life span estimate was 1.8 years, while the von Bertalanffy growth parameter calculated from the tmax was 1.67. These estimates could be used to cropping the fish or obtain desired length class with the highest biomass for harvest, evaluate signs of growth overharvesting, know and prevent mortality at larval or adult stages of fish, indicate poor or good food conversion efficiency, know the life span of the fish thereby informing the time of harvest and thus saving cost of production. All these could be used in the management of the species in aquaculture. (Keywords: life history, length, weight, sexual maturity, photoperiod)